Data transmission through mobile radio links at 1.7 GHz - Sharifah Kamilah Syed Yusof 490467; Tharek Abdul Rahman, 1955- 239614; International Conference on Robotics, Vision and Parallel Processing for Industrial Automation (1994 : USM, Ipoh) 472132
16